Bioefficacy of some new insecticides against mustard aphid, Lipaphis erysimi (Kalt.): BIOEFFICACY OF SOME NEW INSECTICIDES AGAINST MUSTARD APHID - AKSHAY KUMAR SINGH PRATIHAR; M M SUNDRIA; SHALINI PANDEY; RAHUL BHARDWAJ (Journal of Oilseeds Research, 2023)
A field experiment was conducted to evaluate the efficacy of different insecticides against mustard aphid, Lipaphis erysimi (Kalt.) at Research Farm, Agricultural Research Station, Mandor, Jodhpur during rabi, 2021-22. The experiment consists often treatments including untreated control and laid out in randomized block design with three replications. Treatments used in the experiment were dimethoate 30 EC @ 875 ml/ha, thiamethoxam 25 WG @ 100 g/ha, acetamiprid 20 SP @ 50 g/ha, buprofezin 25 SC @ 1000 ml/ha, chlorpyriphos 20 EC @ 500 ml/ha, cyantraniliprole 10.26 OD @ 600 ml/ha, diafenthiuron 50 WP @ 600 g/ha, imidacloprid 17.8 SL @ 100 ml/ha and quinalphos 25 EC @ 1000 ml/ha. Among these treatments imidacloprid 17.8 SL @ 100 ml/ha was found most effective followed by thiamethoxam 25 WG and dimethoate 30 EC while diafenthiuron 50 WP @600 g/ha and chlorpyriphos 20 EC @ 500 ml/ha were reported as least effective treatments. The maximum yield (3861 kg/ha) was recorded in the plot treated with imidacloprid 17.8 SL @ 100 ml/ha followed by thiamethoxam 25 WG (3444 kg/ha) and dimethoate 30 EC (3194 kg/ha). Further, maximum net profit (`2,00,290/ha.) and highest B: C ratio were obtained from imidacloprid 17.8 SL@ 100 ml/ha treated plots while minimumwas obtained in chlorpyriphos 20 EC (2.71:1) treated plots.